BCG Vaccination Status, Age, and Gender as Risk Factors for Leprosy in Endemic Areas in the Brazilian Amazon - Luana Nepomuceno Gondim Costa Lima; Jasna Letícia Pinto Paz; Maria do Perpétuo Socorro Corrêa Amador Silvestre; Letícia Siqueira Moura; Ismari Perini Furlaneto; Karla Valéria Batista Lima (Infectious Disease Reports, 2020)
In 2018, 208,619 new cases of leprosy were reported to the World Health Organization (WHO). Of these, 30,957 occurred in the Americas region and 28,660 (92.6% of the total in the Americas) were reported in Brazil. This study aimed to show the reality of the profile of a population in an endemic leprosy area in northern Brazil in relation to age, gender, and bacillus Calmette–Guérin (BCG) vaccination status through the collection of data in the field with the evaluation of the study individuals, who were recruited by spontaneous demand. A total of 405 individuals participated in the study, with 100 multibacillary, 57 paucibacillary, and 248 healthy contacts. A relationship was observed between the occurrence of the disease, as well as the multibacillary form with the largest age group. The male gender was associated with leprosy per se, with the multibacillary form and was the largest representative of the group that was not vaccinated once. BCG vaccination was effective both in protecting against leprosy per se and in the multibacillary form. These results are limited by sample size, may not be conclusive, and will need further confirmation in a larger cohort.